Representasi Sosial dan Hibriditas Budaya Dalam Sinetron 'Dunia Terbalik': Analisis Televisi Sebagai Medium Budaya Populer - I, Ikrima; Rohmah, Siti; Mardiyyah, Sayyidatul; Sudrajat Nur, Gian Nova (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Television plays a significant role in shaping popular culture by mediatizing social and cultural values. In Indonesia, soap operas like Dunia Terbalik represent rural life while reflecting local values such as solidarity and gotong royong, alongside global elements through cultural hybridity. This study aims to analyze the narratives, characters, and visual elements in Dunia Terbalik to explore how television contributes to social construction and cultural identity amid globalization. Using a qualitative content analysis approach, the findings reveal that the soap opera strengthens cultural identity and creates new cultural forms relevant to modern society, emphasizing television’s role in integrating local values with globalization to reinforce social cohesion and community identity.